Dari Kepatuhan Administratif Ke Pemenuhan Hak Warga: Studi Fenomenologi Penyusunan Standar Pelayanan Pada Pemerintah Kota Mataram - Rido, Muhamad Rosyid; Hidayat, Rahmat Hidayat; Sutarna, Iwan Tanjung (JIAP (Jurnal Ilmu Administrasi Publik), 2026)
The formulation and establishment of service standards require public participation. This study explores the forms and quality of participation and examines the role of citizens through the perspectives of New Public Service and a rights-based approach. Using a qualitative phenomenological method, it captures the experiences of government officials, service users, academics, and NGOs in the licensing and health sectors. The findings show that although participation is formally mandated, it remains largely symbolic because the substance of the standards is centrally determined through OSS and NSPK based on KBLI. This centralization creates an imbalance between local service responsibilities and regional authority, while limited human resources and budgets weaken analytical capacity and the follow-up of participatory inputs. As a result, service standards function more as administrative documents than as dialogic and collaborative social contracts, underscoring the need for more participatory, contextual, and rights-oriented public service policies.